The Convergence Theory on ICT, Society and Human Beings – towards the Good ICT society - Gunilla Bradley (tripleC: Communication, Capitalism & Critique)
The convergence model illustrates ongoing changes in the Net Society. However the theoretical model goes back and synthesises the theoretical framework in research on psychosocial work environment and computerization. Interdisciplinary research programs were initiated by the author in the 70th and then analyzed changes in society related to various periods in “the history” of ICT. The description of the convergence model is structured with reference to the concepts Globalization, ICT, Life Environment, Life Role, Effects on Humans. Both Convergence and Interactions are important features in the model.  There are four levels of analysis – individual, organisational, community, and societal.